Students’ learning activities and science process skills: The effectiveness of group investigation learning model - Nur Hayati; Mucharommah Sartika Ami (STKIP Persada Khatulistiwa Sintang, 2022)
Science learning should prioritize the development of process skills rather than science products because these skills are needed in carrying out the scientific method. Science process skills can be achieved if students are actively involved in learning. One of the learning models that involve student activities is the Group Investigation (GI). This study aims to determine the effectiveness of the GI learning model in practicing students' learning activities and science process skills on additives material at grade VIII. This research is a classroom action research which consists of two cycles. Each cycle consists of planning, implementing, observing and reflecting stages. The research subjects consisted of 30 students. The instrument used was the observation sheet of student activities and science process skills. Data analysis was carried out descriptively qualitatively. The results of this study indicate that student learning activity in the cycle I is 73.3% (